The Implementation of E-Commerce for Frozen Food Products in Providing Recommendations Using Item-Based Collaborative Filtering Method - Simanungkalit, Racquel Terranova; Triayudi, Agung; Benrahman (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2024)
The development of information technology, especially the internet, has significantly impacted facilitating human access to information, including the trend of society opting for frozen food as a fast food option. Meanwhile, the phenomenon of social media depicts the tendency of society to choose convenient and fast food. On the other hand, the rapid development of sales and product promotion systems through the internet is taking place, utilizing web-based technology. Recent studies also indicate that the development of web-based sales information systems for frozen food can enhance efficiency and service quality. Collaborative filtering methods in recommendation systems are also becoming increasingly popular in helping users obtain better recommendations. All of this indicates that information technology has had a positive impact on making purchasing and information management more efficient and convenient for society